THE EFFECT OF NUTRITION ASSISTANCE PROGRAMS ON EATING ORDER PATTERNS AND NUTRITIONAL STATUS IN KALIBUNTU VILLAGE: The Effect Of Nutrition Assistance Programs On Eating Order Patterns And Nutritional Status In Kalibuntu Village - Tutik Hidayati (LPPM - STIKES Pemkab Jombang, 2019)
The problem of malnutrition in children under five is still a major health problem in the world, including Indonesia. Indonesia is a developing country that still faces considerable problems of malnutrition. Nutritional problems nationally are under-five and under-nutrition children under five. Poor nutritional status is a condition of the body experiencing nutritional deficiencies or below standard. Based on the nutritional status monitoring (PSG) survey in Probolinggo District, there was an increase in cases of malnutrition, obtained in the prevalence of non-compliance with the weight per year in 2017 of 9.44%, an increase compared to 2016, namely 8.65% under-five children under five. Toddlers are considered the biggest nutritional risk because patterns of poor feeding have an impact on growth and development. This causes the toddler age group to increase the risk of morbidity and mortality. Based on a preliminary study in April 2018, data was obtained that Probolinggo was ranked second in the area of ??malnutrition in East Java. In 2017 there are 130 toddlers who experience malnutrition in the Kalibuntu Coast of Probolinggo Regency. The cause of malnutrition is due to the pattern and intake of toddlers' food which contains less nutrition.The purpose of this study was to analyze the effect of nutritional support programs on feeding patterns and nutritional status of the Kalibuntu Coastal Children in Probolinggo Regency. This research is an experimental study, namely by measuring the increase / comparison of feeding patterns and nutritional status before and after the nutrition companion program. The population in this study were all toddlers with malnutrition in the Kalibuntu Coast of 130 people in Probolinggo Regency. Sampling uses Total Sampling. Samples are all mothers who have underweight and malnourished children under the age of 130 people in the Kalibuntu Coast of Probolinggo Regency. Data collection using observation sheets and interviews. Analysis of univariate data using frequency distribution, bivariate analysis using Wilcoxon match paired test and multivariate analysis using multiple linear regression then drawn conclusions. The results of the Wilcoxon match paired test between nutritional companions on feeding patterns obtained a p value of 0,000 <? 0,05, so ha was accepted so that there was an effect of nutritional companion on feeding patterns. The value of Exp (B) in the logistic regression analysis of eating parenting has a value of 85.008, which means that parenting has a chance of 85,008 times to change. While the nutritional status variable in multiple logistic regression has an Exp (B) value of 3.663, from these results it can be explained that nutritional status has an opportunity to increase 3.663 times.